Frugal innovation: Antecedents, mediators, and consequences - Mokter Hossain (14634969) (2023)
Frugal innovation (FI) describes a phenomenon whereby solutions are developed to serve low-income customers, mainly in developing countries, with affordable products and services that help address pressing social and environmental problems. Despite a decade of academic interest in FI, we still lack an overarching understanding of the various facets of this phenomenon. Based on 48 in-depth interviews for 23 cases, we integrated and validated 10 years of FI scholarship. This study therefore set out to develop a comprehensive framework for FI, one that would identify its antecedents, mediators, and consequences. Such a framework promises a holistic perspective for FI by linking these identified factors to the concept of sustainability. The findings also reinforce the dual contribution that FI makes in terms of both business growth and inclusive growth. Finally, this study discusses the theoretical and practical implications and provides some suggestions for future research on FI.  Other Information Published in: Creativity and Innovation Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/caim.12511